2015
DOI: 10.1063/1.4913824
|View full text |Cite
|
Sign up to set email alerts
|

Electron collisions with phenol: Total, integral, differential, and momentum transfer cross sections and the role of multichannel coupling effects on the elastic channel

Abstract: We report theoretical and experimental total cross sections for electron scattering by phenol (C6H5OH). The experimental data were obtained with an apparatus based in Madrid and the calculated cross sections with two different methodologies, the independent atom method with screening corrected additivity rule (IAM-SCAR), and the Schwinger multichannel method with pseudopotentials (SMCPP). The SMCPP method in the Nopen-channel coupling scheme, at the static-exchange-plus-polarization approximation, is employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 42 publications
3
37
1
Order By: Relevance
“…In addition, Neves et al 21 found some evidence for a higher-lying shape resonance enhancing the phenol cross sections vis à vis those of benzene. Support for the existence of that resonance was also found in our Schwinger Multichannel Method with Pseudo-potentials (SMCPP) calculations for the elastic channel 20 and our experimental total cross section measurements. 20 As the decay of a resonance into a given scattering channel or channels is often most easily seen through the measurements of excitation functions or integral cross sections, 31 we were thus also interested to see if the proposed resonance manifested itself in our vibrational-mode and electronic-state ICSs.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…In addition, Neves et al 21 found some evidence for a higher-lying shape resonance enhancing the phenol cross sections vis à vis those of benzene. Support for the existence of that resonance was also found in our Schwinger Multichannel Method with Pseudo-potentials (SMCPP) calculations for the elastic channel 20 and our experimental total cross section measurements. 20 As the decay of a resonance into a given scattering channel or channels is often most easily seen through the measurements of excitation functions or integral cross sections, 31 we were thus also interested to see if the proposed resonance manifested itself in our vibrational-mode and electronic-state ICSs.…”
Section: Introductionmentioning
confidence: 54%
“…1 for the CH-stretch and CH-stretch overtone (2 × CHstretch) being consistent with that observation. We had previously observed that there is some evidence, in our elastic cross section calculations 3,20 and total cross section measurements, 20 for the existence of a broad shape resonance for incident electron energies in the ∼10-20 eV range. Further support for this notion can be found in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations